2023
DOI: 10.1109/access.2023.3258179
|View full text |Cite
|
Sign up to set email alerts
|

Class-Adaptive Data Augmentation for Image Classification

Abstract: Data augmentation is a widely used regularization technique for improving the performance of convolutional neural networks (CNNs) in image classification tasks. To improve the effectiveness of data augmentation, it is important to find label-preserving transformations that fit the domain knowledge for a given dataset. In several real-world datasets, appropriate augmentation policies differ between classes, owing to their different characteristics. In this paper, we propose a class-adaptive data augmentation me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…This method involves the creation of a more extensive and diverse set of training data by randomly transforming images. Due to its high efficacy, data augmentation has become a frequently employed technique for enhancing classification accuracy across a range of image classification tasks [ 28 ]. The current study observed an imbalance in the number of pods and seeds among 20 types of soybean materials, as shown in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…This method involves the creation of a more extensive and diverse set of training data by randomly transforming images. Due to its high efficacy, data augmentation has become a frequently employed technique for enhancing classification accuracy across a range of image classification tasks [ 28 ]. The current study observed an imbalance in the number of pods and seeds among 20 types of soybean materials, as shown in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…It involves generating additional data to enhance the training process, improve model performance and generalization. Augmenting the training dataset involves applying various transformations to the original images, creating new variations such as rotation, flipping, zooming, translation, brightness and contrast adjustment, Gaussian noise (adding a small amount of Gaussian noise to the images to make the model more robust to noise), elastic deformations (applying elastic deformations to the images to introduce distortions, making the model more tolerant to deformations in the input data), color jittering (randomly change the hue, saturation and brightness of the images to introduce variations in color), random cropping (a portion of the image, forcing the model to focus on different regions) and shearing (apply shearing transformations to the images, simulating changes in the viewing angle) [116][117][118]. These processes help the model become more robust by exposing it to different perspectives, orientations and conditions.…”
Section: Data Augmentation For Training a Robust Cnn Diagnostic Model...mentioning
confidence: 99%
“…In general, the training dataset available for Parkinson's disease detection tasks does not adequately encompass the variations in hand movements. To overcome this problem, numerous researchers in many fields of research have resorted to the use of the data augmentation method to develop more training samples and model the variation of a given person [42].…”
Section: A Data Augmentationmentioning
confidence: 99%